Public Policies in the Pandemic: Bibliometric Analysis in the Brazilian Context on the Web of Science and Scopus (Research, Society and Development, 2021)
The Corona Virus pandemic brought serious problems of a world order, which involve the most varied activities of society causing disorder and increased social entropy. In this sense, governments and institutions have implemented public policies with the objective of minimizing the impacts of the disease and, simultaneously, these experiences have generated an increase in scientific production on the subject. Therefore, the objective of this work is to show the academic relevance of scientific productions on public policies in the pandemic through a bibliometric analysis. The study was carried out in the Web of Science and Scopus databases. It enabled the construction of a bibliographic portfolio with 39 relevant articles aligned with the theme. In addition to the selected articles that serve as a theoretical framework on the topic in question, the most relevant scientific productions from InOrdinatio stand out, which considers the impact factor, number of citations and year of publication. The study also uses cluster analysis as a multivariate classification technique and VOSviewer software for bibliographic mapping.